Impact of graded compression stockings on deep vein thrombosis incidence after fast-track total knee arthroplasty: a retrospective cohort study - Dengxian Wu; Kai Fu; Gongan Jiang; Liang Qiao; Yao Yao; Dongyang Chen; Qing Jiang (BMC Musculoskeletal Disorders)
Abstract Background Venous thromboembolism (VTE) is a significant complication following total knee arthroplasty (TKA), with considerable implications for patient outcomes. The purpose of this study is to assess the incidence of VTE after fast-track TKA at our center and to evaluate whether the use of graded compression stockings (GCS) can further reduce VTE incidence within this regimen. Methods A total of 660 patients undergoing primary TKA between January 1, 2018, and December 31, 2022, were included. Patients were categorized into two groups: GCS group (n = 390) and non-GCS group (n = 270). Knee-length GCS were applied to patients in the GCS group. Diagnosis of deep vein thrombosis (DVT) was confirmed by bilateral lower extremity duplex venous ultrasonography. Incidence and locations of thrombosis were recorded. Demographic characteristics, laboratory indices, and surgical variables were collected. Univariate and multivariate regression analyses were performed to identify risk factors for thrombosis. Results The overall incidence of VTE after fast-track TKA was 6.2% (41/660), with no cases of proximal DVT or pulmonary embolism (PE). The incidence of DVT was significantly lower in the GCS group compared to the non-GCS group (3.8% vs. 9.6%). After adjusting for confounders, multivariate analysis demonstrated that absence of GCS, older age, and history of cardiovascular disease were independent risk factors for postoperative DVT. Conclusion In conclusion, this study found a low incidence of VTE after fast-track TKA, and the use of GCS may further reduce the occurrence of early postoperative calf muscular vein thrombosis (CMVT) when combined with anticoagulants plus intermittent pneumatic compression (IPC).